Antioxidant properties of natural compounds used in popular medicine for gastric ulcers - Repetto,M.G. (2002)
There is evidence concerning the participation of reactive oxygen species in the etiology and physiopathology of human diseases, such as neurodegenerative disorders, inflammation, viral infections, autoimmune pathologies, and digestive system disorders such as gastrointestinal inflammation and gastric ulcer. The role of these reactive oxygen species in several diseases and the potential antioxidant protective effect of natural compounds on affected tissues are topics of high current interest. To consider a natural compound or a drug as an antioxidant substance it is necessary to investigate its antioxidant properties in vitro and then to evaluate its antioxidant functions in biological systems. In this review article, we shall consider the role of natural antioxidants derived from popular plants to reduce or prevent the oxidative stress in gastric ulcer induced by ethanol.